Assessing resilience and state‐transition models with historical records of cheatgrass Bromus tectorum invasion in North American sagebrush‐steppe. Issue 5 (17th July 2013) - Bagchi, Sumanta; Briske, David D.; Bestelmeyer, Brandon T.; Ben Wu, X.
Summary: Resilience‐based approaches are increasingly being called upon to inform ecosystem management, particularly in arid and semi‐arid regions. This requires management frameworks that can assess ecosystem dynamics, both within and between alternative states, at relevant time scales. We analysed long‐term vegetation records from two representative sites in the North American sagebrush‐steppe ecosystem, spanning nine decades, to determine if empirical patterns were consistent with resilience theory, and to determine if cheatgrass Bromus tectorum invasion led to thresholds as currently envisioned by expert‐based state‐and‐transition models (STM). These data span the entire history of cheatgrass invasion at these sites and provide a unique opportunity to assess the impacts of biotic invasion on ecosystem resilience. We used univariate and multivariate statistical tools to identify unique plant communities and document the magnitude, frequency and directionality of community transitions through time. Community transitions were characterized by 37–47% dissimilarity in species composition, they were not evenly distributed through time, their frequency was not correlated with precipitation, and they could not be readily attributed to fire or grazing. Instead, at both sites, the majority of community transitions occurred within an 8–10 year period of increasing cheatgrass density, became infrequent after cheatgrass density peaked, and thereafter transition frequency declined. Greater cheatgrass density, replacement of native species and indication of asymmetry in community transitions suggest that thresholds may have been exceeded in response to cheatgrass invasion at one site (more arid), but not at the other site (less arid). Asymmetry in the direction of community transitions also identified communities that were 'at‐risk' of cheatgrass invasion, as well as potential restoration pathways for recovery of pre‐invasion states. Synthesis and applications . These results illustrate the complexities associated with threshold identification, and indicate that criteria describing the frequency, magnitude, directionality and temporal scale of community transitions may provide greater insight into resilience theory and its application for ecosystem management. These criteria are likely to vary across biogeographic regions that are susceptible to cheatgrass invasion, and necessitate more in‐depth assessments of thresholds and alternative states, than currently available. Abstract : These results illustrate the complexities associated with threshold identification, and indicate that criteria describing the frequency, magnitude, directionality and temporal scale of community transitions may provide greater insight into resilience theory and its application for ecosystem management. These criteria are likely to vary across biogeographic regions that are susceptible to cheatgrass invasion, and necessitate more in‐depth assessments of thresholds and alternative states, than currently available.